Carbon Capture and Storage (CCS) policy for China: Implications from Some Representative Countries and Regions - Wu, Xudong; Yang, Qing; Wu, Tianhua; Chen, Guoqian (Journal of Environmental Accounting and Management, 2026)
In recent years carbon capture and storage (CCS) emerged as a promising low-carbon technology to tackle climate change by storing the captured CO2 underground. Varied countries and regions have promulgated or proposed specific CCS policies to accommodate with CCS development in their jurisdictions. However, CCS policies seem to be in a vacancy in China. Presented in this paper is a general overview for CCS policies in some representative countries and regions including the United States, Canada, United Kingdom and Australia that are making substantial contributions to the establishment of CCS policy framework in their own jurisdictions as well as their implications for construction of CCS policy framework in China. CCS policies in China are also reviewed and compared with those of the typical economic entities in detail. The result demonstrates that prescriptive standards and regulations, economic incentives as well as supportive measures are not sufficient to smooth CCS deployment in China. Policy recommendations are thus raised to guide CCS progress in China, with a suggested policy package including enactment of CCS regulatory framework, multi-source funding mechanism, elaborated measures to raise public awareness of CCS. The outcome has essential policy implications supportive to a further expansion of CCS deployment in China.